2020
DOI: 10.1002/elan.202060425
|View full text |Cite
|
Sign up to set email alerts
|

Development of Apple Tissue Based Biocathode and MWCNT−Pt−Au Nanomaterial Based Bioanode Biofuel Cell

Abstract: A biofuel cell (BFC) was fabricated by combining multiwalled carbon nanotube ‐platinum‐gold (MWCNT−Pt−Au) hybrid nanomaterial, glucose oxidase (GOx) and benzoquinone included carbon felt electrode (CFE) bioanode with apple tissue included CFE biocathode. The working parameters of bioanode were optimized both experimentally and chemometrically. For the biocathode, apple, banana and pear tissues were tried and best power output was obtained with apple tissue. By combining MWCNT−Pt−Au/GOx/CFE bioanode with apple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…For this purpose, activated MWCNTs were used. First of all, in order to perform the acid activation procedure, the proper amount of MWCNT powder was sonicated in 40 mL of acid mixture including H 2 SO 4 /HNO 3 (3:1 v/v) for 6 h. After that, the activated MWCNT powder was rinsed with pure water, centrifuged, and then dried in a vacuum oven at 50 • C for 14 h. Then, platinum nanoparticle (PtNP) and gold nanoparticle (AuNP) or only AuNP deposition procedure on MWCNT was started with the sonication of 20 mg activated MWCNT in the presence of 20 mL of the Au and Pt nanoparticle solutions (for MWCNT-Au-Pt) or only AuNp (for MWCNT-Au) solution, which were prepared according to previous studies [35,36]. After the sonication step for 4 h, the mixture was annealed at 150 • C for 4 h to increase functionality.…”
Section: Mwcnt-based Hybrid Nanomaterials Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, activated MWCNTs were used. First of all, in order to perform the acid activation procedure, the proper amount of MWCNT powder was sonicated in 40 mL of acid mixture including H 2 SO 4 /HNO 3 (3:1 v/v) for 6 h. After that, the activated MWCNT powder was rinsed with pure water, centrifuged, and then dried in a vacuum oven at 50 • C for 14 h. Then, platinum nanoparticle (PtNP) and gold nanoparticle (AuNP) or only AuNP deposition procedure on MWCNT was started with the sonication of 20 mg activated MWCNT in the presence of 20 mL of the Au and Pt nanoparticle solutions (for MWCNT-Au-Pt) or only AuNp (for MWCNT-Au) solution, which were prepared according to previous studies [35,36]. After the sonication step for 4 h, the mixture was annealed at 150 • C for 4 h to increase functionality.…”
Section: Mwcnt-based Hybrid Nanomaterials Preparationmentioning
confidence: 99%
“…Therefore, sensitive, accurate, and practical systems for swine flu diagnosis are tremendously needed. To date, electrochemical immunosensors containing many different modifying materials have been developed for the detection of H1N1 [14,35]. Veerapandian et al reported the development of an electrochemical sensor platform composed of methylene blue-electro-adsorbed graphene oxide nanostructures modified with monoclonal antibodies against the H proteins of H1N1 [36].…”
Section: Introductionmentioning
confidence: 99%